2002
DOI: 10.1094/pdis.2002.86.12.1315
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Peanut to Sclerotinia Blight and the Effect of Acibenzolar-S-methyl and Fluazinam on Disease Incidence

Abstract: Sclerotinia minor, a soilborne fungal pathogen of peanut, can cause serious yield loss in North Carolina. A field test was implemented to study genotype reaction, and the effect of aciben-zolar-S-methyl (a plant activator) and the fungicide fluazinam on disease incidence. In all, 13 genotypes in 1997 and 12 genotypes in 1998 were evaluated. Three applications of acibenzolar-S-methyl (0.14 kg a.i./ha) or fluazinam (0.58 kg a.i./ha) were made on a calendar-based schedule. Disease ratings were made weekly in 1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Fluazinam is considered a protectant (Lemay et al, 2002;Vitoratos, 2014) and must be applied prior to disease onset for best results, which typically coincides with first bloom and an additional application may be necessary if the favorable conditions to white mold continues (Paula Júnior et al, 2009b). The mode of action of fluazinam is uncoupling of mitochondrial oxidative phosphorylation, consequently halting synthesis of ATP without affecting the respiratory chain and ATP synthesis (Guo et al, 1991;Vitoratos, 2014).…”
mentioning
confidence: 99%
“…Fluazinam is considered a protectant (Lemay et al, 2002;Vitoratos, 2014) and must be applied prior to disease onset for best results, which typically coincides with first bloom and an additional application may be necessary if the favorable conditions to white mold continues (Paula Júnior et al, 2009b). The mode of action of fluazinam is uncoupling of mitochondrial oxidative phosphorylation, consequently halting synthesis of ATP without affecting the respiratory chain and ATP synthesis (Guo et al, 1991;Vitoratos, 2014).…”
mentioning
confidence: 99%
“…Fluazinam is one of the most effective fungicides for controlling Sclerotinia diseases (Lemay et al 2002;Mahoney et al 2014;Matheron and Porchas 2004;Vieira et al 2012). This fungicide has activity at multiple sites and, therefore, risk of resistance development is low .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the effect of fungicide application method on soilborne fungal disease incidence in peanuts (Sturgeon, 1990;Brenneman et al, 1991;Smith et al, 1992;Brenneman and Culbreath, 1994;Damicone and Jackson, 2001;Lemay et al, 2002). Sturgeon (1990) reported that southern blight incidence in peanuts was reduced when fungicide was applied in conjunction with a canopy opener.…”
Section: Discussionmentioning
confidence: 99%